Avaliação do PRONAF-A no Assentamento Banhos, no Município de Morada Nova – Ceará - Silva, Osias Pereira da (2010)
The proposal this study was to evaluate the effects of the National Program to Strengthen Family Agriculture (PRONAF), in the form intended for agrarian reform settlers Pronaf A, in the productive capacity in Assentamento Banhos em Morada Nova - CE. The study considered the The methodology utilized bibliographical and documental research as well as a qualitative and quantitative field research. The research results show that Pronaf A was responsible for increasing productive capacity in the settlement, given that the higher the planted area of 2.3 to 4.5 ha, increasing production and productivity of agricultural activities financed, diversification of activities explored, contributed to maintenance of 28 direct jobs. The study also showed that there should be greater monitoring and control by financial institutions and technical assistance to maintain the effectiveness of the program and the need for intersectoral programs both aimed specifically at rural areas as well as offer public service of health, transportation and education.